Electric mobility of Indonesia: a strategy for achieving net zero emission by 2050 - Listijorini, Erny; Kanani, Nufus; Purwamargapratala, Yustinus; Satria, Dhimas; Sukamto, Dwinanto; Lusiani, Rina; Yusuf, Yusvardi; Jannah, Miftahul; Abdullah, Syarif; Pinem, Mekro Permana (Jurnal Teknika, 2023)
Electric mobility mode could be a great opportunity to reduce emissions from the transportation sector. The future mobility calculator and electric car power demand, developed by Coalition for Urban Transitions and International Energy Agency, respectively, were used to analyze Indonesia’s shifting strategy toward electric mobility. It was shown that going to electric mobility will reduce 90% of Indonesia’s emissions from the transportation sector by the year 2050. Nevertheless, the charging infrastructure must be improved quickly to provide a proper ecosystem for electric mobility. Additionally, the electric vehicle waste management system is urgently needed soon. The success of shifting toward electric mobility not only benefits Indonesia’s environment but also strengthens its international credibility for sustainable development.